Examining the Auditors’ Acceptance of Big Data Analytics Technology Platform: Evidence from Government Auditors in Indonesia - Fauzan Wahyuabdi Pratama; Erna Fitri Komariyah (The Indonesian Journal of Accounting Research, 2023)
This study examines the determinants of auditors’ acceptance of big data analytics (BDA) technology. Using the responses from 83 government auditors, we test the model built from the Unified Theory of Acceptance and Usage of Technology (UTAUT) theory and trust. The respondents are auditors who attended the BDA technology training session and have access to this technology. We utilize Structural Equation Modeling (SEM) as a data analytic method aided by SmartPLS 3 software. This study finds that three constructs in UTAUT, i.e., effort expectancy, performance expectancy, and facilitating condition, influence auditors' acceptance of BDA technology; meanwhile, one construct in UTAUT, social influence, does not influence auditors' acceptance of BDA technology. The additional construct, trust, also does not influence auditors’ acceptance of BDA technology. This study offers novelty to the literature in the context of BDA technology adoption as a current innovative technology in the auditing field. This study advises government audit agencies to develop technology that is easy to adopt, provides benefits of increased audit quality, and sufficient technical and infrastructure support.